AToMS: A Ubiquitous Teleconsultation System for Supporting AMI Patients with Prehospital Thrombolysis - Bruno S. P. M. Correa; Bernardo Gonçalves; Iuri M. Teixeira; Antônio T. A. Gomes; Artur Ziviani (International Journal of Telemedicine and Applications)
The latest population-based studies in the medical literature worldwide indicate that acute myocardial infarction (AMI) patients still experience prolonged delay to be rescued, which often results in morbidity and mortality. This paper reports from a technological standpoint a teleconsultation and monitoring system named AToMS. This system addresses the problem of prehospital delivery of thrombolysis to AMI patients by enabling the remote interaction of the paramedics and a cardiologist available at a Coronary Care Unit (CCU). Such interaction allows the diagnosis of the patient eligibility to the immediate application of thrombolysis, which is meant to reduce the delay between the onset of symptoms and the eventual application of proper treatment. Such delay reduction is meant to increase the AMI patient's chances of survival and decrease the risks of postinfarction sequels. The teleconsultation is held with the support of wireless and mobile technologies, which also allows the cardiologist to monitor the patient while he/she is being taken to the nearest CCU. All exchanged messages among paramedics and cardiologists are recorded to render an auditable system. AToMS has been deployed in a first stage in the city of Rio de Janeiro, where the medical team involved in the project has conducted commissioned tests.